Predictors of Severity of Scrub Typhus in Children Requiring Pediatric Intensive Care Admission - Khemka, Arpita; Sarkar, Mihir; Basu, Ankika; Dey, Partha Pratim; Chowdhoury, Satyabrata Roy; Mandal, Kalyanbrata (Journal of Pediatric Intensive Care, 2021)
Objective of our study was to determine the clinical characteristics and laboratory profile of scrub typhus patients requiring pediatric intensive care admission and to find out risk factors for the severity of illness. This was a cross-sectional observational study conducted on 1-month to 12-year-old children admitted with scrub typhus in a tertiary care pediatric intensive care unit (PICU). Relevant demographic, clinical, laboratory, treatment, and outcome-related data were documented. The severity of the disease was measured in the form of multiple organ dysfunction syndrome (MODS). With further correlation, and univariate and multivariate analyses, factors associated with severe disease were identified. During the study period, out of 586 PICU admission, 62 patients (10.6%) were diagnosed with scrub typhus. The mean age was 63.85 ± 52.78 months, where infants constituted 32.3% of the total population. Fever was present in 100% of the cases. Common indications of PICU admission were: respiratory distress 42 (67.7%), altered sensorium 41 (66.1%), convulsion 37 (59.7%), and shock 31 (50%). Total number of patients with MODS was 40 (64.5%). The case fatality rate was 8%. On multivariate analysis, infant age group (p = 0.02), altered sensorium (p = 0.001), reduced urine output (p = 0.02), thrombocytopenia (p = 0.001), raised C-reactive protein (p = 0.004), hyponatremia (p = 0.005), hypoalbuminemia (p = 0.01), deranged international normalized ratio (p = 0.02), and hyperferritinemia (p = 0.02) came out to be independent factors in predictability for development of MODS. Multiorgan dysfunction is a life-threatening manifestation of scrub typus in children, which necessitates PICU admission. Infant age group, presence of altered sensorium, reduced urine output, thrombocytopenia, elevated inflammatory markers, coagulopathy, hypoalbuminemia, and hyponatremia predict risk for MODS.
Keywords: scrub typhus; severe disease; pediatric intensive care unit; risk factors